Komunikasi Ritual Dalam Pencak Silat (Studi Kasus Pada Pencak Silat Cimande Kecamatan Caringin Kabupaten Bogor) - Muhamad Rizki Sya’bana; Asep Gunawan; Yono Yono (KOLONI, 2023)
Cimande Pencak Silat is a traditional Indonesian martial art that has many fans and practitioners in various regions in Indonesia. Ritual communication is related to traditions and culture that develop within society, which is also used to study interactions in traditions or culture such as pencak silat. This research aims to determine the ritual communication model and Islamic values ​​contained in the pencak silat aspect. This research uses a qualitative approach method. The data sources in this research are divided into two, namely primary data and secondary data. Data analysis uses interactive techniques miles & huberman. The research results show that the ritual communication model in Cimande pencak silat uses an interactional communication model in the form of interaction between individuals or groups and connecting with Allah SWT through symbols, readings, deep meanings. The Islamic values ​​in movements, readings, rules and attributes in Pencak Silat Cimande were formed with the main aim of preaching to the wider community in order to shape the individual character of students and society and teach positive traits. Pencak Silat Cimande also teaches the importance of humility and submission to God.